The Impact of Work-Life Balance and Job Satisfaction on Employee Productivity - Cahyanuzul, Pramaesty Adinda; Handayani, Susi; Afriyani, Fauziah (Manunggal Halim Jaya, 2025)
Employee productivity is an important factor in a company's success, especially in an increasingly tight business competition era. This study analyzes the impact of work-life balance and job satisfaction on PT. Brilliant Think Center employee productivity. The research method used is quantitative with a descriptive approach. Data were collected by distributing questionnaires to 94 PT Brilliant Think Center employees and analyzed using multiple linear regression. The study results show that work-life balance significantly affects employee productivity, where the balance between work and personal life increases efficiency and work motivation. Not only that, job satisfaction also has a positive impact on employee productivity, especially in increasing loyalty and work enthusiasm. Simultaneously, both variables contribute significantly to increasing employee productivity. This finding proves companies that support and create a more comfortable and motivating work environment. Thus, it is hoped that employee productivity can continue to increase, which ultimately positively impacts the company's growth.